Who benefited from the disclosure mandates of the 1964 Securities Acts Amendments? - Battalio, Robert; Hatch, Brian; Loughran, Tim (Journal of Corporate Finance, 2011)
The 1964 Securities Acts Amendments extended disclosures mandated of NYSE firms to most firms trading in the Over-the-Counter (OTC) market. Although some prior evidence suggests substantial value increases for OTC firms due to the “value enhancing” mandated disclosures, we find no statistical difference in announcement returns for OTC firms moving to the NYSE before and after the legislation. One purported advantage to investors from the 1964 legislation was increased financial reporting. Yet, we document that the bulk of OTC firms analyzed in prior studies was already providing investors financial information before the legislation. Apparently, investors did not value the mandated disclosures. We do find evidence that the NYSE benefited from the legislation by increasing the number of OTC firms switching to their exchange around its passage.